KAJIAN POLITIK HUKUM UNDANG-UNDANG NOMOR 3 TAHUN 2020 TENTANG PERTAMBANGAN MINERAL DAN BATUBARA TERHADAP KEWAJIBAN PENGOLAHAN DAN PEMURNIAN HASIL PENAMBANGAN DI DALAM NEGERI - EVANGELISTA, BEVERLY (GANEC SWARA, 2024)
With the issuance of Law no. Law No. 3 of 2020 replaces Law No. 4 of 2009 concerning Mineral and Coal Mining. It is hoped that it will position the Indonesian state as the sovereign party over its natural resources. Therefore, it is necessary to formulate the problem, namely how to study the legal politics of Law No. 3 of 2020 concerning Mineral Mining. And Coal towards the obligation to process and refine mining products domestically. The research method is normative with several approaches, namely the Conceptual Approach and the Statute Approach. From the results of the author's research, it was found that the government considers it necessary to increase the added value of minerals through domestic mineral resource processing and refining activities, as intended in Article 103 and Article 170 of Law Number 3 of 2020 concerning Mineral and Coal Mining, so the government then promulgate Government Regulation (PP) No. 96 of 2021 which is an amendment to PP No. 1 of 2014 concerning Implementation of Mineral and Coal Mining Business Activities. One of the important regulations in this PP is the obligation to carry out 100% mineral refining domestically so that there will be no more exports of raw minerals by mining companies. The aim of banning exports of raw minerals is to increase fiscal added value while creating jobs. Because mining companies are required to build processing plants or smelters in the country. In this way, new job opportunities will be opened for the Indonesian people